Prevalence of potential interactions of medications, including herbs and supplements, before, during, and after chemotherapy in patients with breast and prostate cancer. Issue 11 (1st February 2021) - Lee, Richard T.; Kwon, Nancy; Wu, Jimin; To, Connie; To, Steven; Szmulewitz, Russell; Tchekmedyian, Raffi; Holmes, Holly M.; Olopade, Olufunmilayo I.; Stadler, Walter M.; Von Roenn, Jamie
Abstract : Background: The use of herbs and supplements (HS) is common among patients with cancer, yet limited information exists about potential medication interactions (PMIs) with HS use around chemotherapy. Methods: Patients with breast or prostate cancer who had recently finished chemotherapy at 2 academic medical centers were surveyed by telephone. Interviewers inquired about all medications, including HS, before, during, and after chemotherapy. Micromedex, Lexicomp, and Natural Medicines Comprehensive Database interaction software programs were used to determine PMIs. Results: A total of 67 subjects (age range, 39‐77 years) were evaluated in this study. Participants were primarily White patients (73%) with breast cancer (87%). The median number of medications was 11 (range, 2‐28) during the entire study and was highest during chemotherapy (7; range, 2‐22). Approximately four‐fifths (84%) used HS. A total of 1747 PMIs were identified, and they represented 635 unique PMIs across all 3 timeframes, with most occurring during chemotherapy. Prescription‐related PMIs (70%) were the most common type, and they were followed by HS‐related (56%) and anticancer treatment–related PMIs (22%). Approximately half of the PMIs (54%) were categorized as moderate interactions, and more than one‐third (38%) were categorized as major interactions. Patient use of HS increased from 51% during chemotherapy to 66% after chemotherapy, and this correlated with an increased prevalence of HS PMIs (46% to 60%). HS users were more likely to be at risk for a major PMI than non‐HS users (92% vs 70%; P = .038). Conclusions: The use of HS remains prevalent among patients with cancer and may place them at risk for PMIs both during chemotherapy and after the completion of treatment. Lay Summary: This study evaluates the risk of potential medication interactions for patients with breast or prostate cancer undergoing chemotherapy. The results show that patients often use herbs and supplements during treatment. Prescription medications are most often associated with medication interactions, which are followed by herb and supplement–related interactions. More than one‐third of potential medication interactions are considered major. Patients should be educated about the risk of herb and supplement–related medication interactions during treatment. Abstract : Patients with cancer receiving chemotherapy commonly use herbs and supplements. Some of these products are associated with potential medication interactions.